2020
DOI: 10.1080/23328940.2020.1769530
|View full text |Cite
|
Sign up to set email alerts
|

Human white-fat thermogenesis: Experimental and meta-analytic findings

Abstract: White adipose tissue (WAT) thermogenic activity may play a role in whole-body energy balance and two of its main regulators are thought to be environmental temperature (T env) and exercise. Low T env may increase uncoupling protein one (UCP1; the main biomarker of thermogenic activity) in WAT to regulate body temperature. On the other hand, exercise may stimulate UCP1 in WAT, which is thought to alter body weight regulation. However, our understanding of the roles (if any) of T env and exercise in WAT thermoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Upon its discovery, irisin has been a subject of intense investigation [15]. Since irisin is an exercise-induced hormone [6] and passes a signal to AT, it is important to identify the molecular mechanisms that mediate its effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon its discovery, irisin has been a subject of intense investigation [15]. Since irisin is an exercise-induced hormone [6] and passes a signal to AT, it is important to identify the molecular mechanisms that mediate its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Irisin is an adipo-myokine secreted mainly by skeletal muscle and by AT, after the proteolytic cleavage of fibronectin type III domaincontaining protein 5 (FNDC5) [6]. Physical activity induces the expression of irisin through the activation of the transcriptional factor peroxisome proliferator-activated receptor γ (PPARγ), the coactivator-1α (PGC-1α) and of FNDC5 [15,23]. These pathways are involved in the browning of WAT [50].…”
Section: Introductionmentioning
confidence: 99%
“…Both in vivo and in vitro models are necessary to effectively understand the mechanisms involved in the browning process. This is demonstrated by the controversy observed between in vivo human and animal studies regarding exercise-induced adipose tissue browning, which is likely caused by a variability in the exercise protocols used and different methods of browning detection [23]. Moreover, exercise exerts many whole-body adaptations, which are difficult to study separately through in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies using similar exercise protocols reported that exercise upregulated the browning process, but without any positive effects on the metabolism of the volunteers [16]. This stark controversy between animal and human studies with respect to the impact of exercise on the browning process has been demonstrated in a recent series of meta-analyses [23] and has been attributed to (i) heterogeneity of white adipose tissue depots [17], (ii) the variability in sample collection in animals and, mainly, humans [17,24], and (iii) a host of external factors (e.g., nutrition, environmental temperature, other stressors) that may interfere with the effect of exercise on the browning process [6,23]. Therefore, there is a need for in vitro experiments aiming to identify the factors and the procedures which can induce browning of white lipocytes under the effect of exercise.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, body mass index (BMI) [15], age [16] and fat mass [1] are inversely associated with BAT activity. This is not surprising, since BMI and fat mass are inversely associated with white adipose tissue thermogenic activity in humans [17].…”
Section: Introductionmentioning
confidence: 91%